2015
DOI: 10.1074/jbc.m115.657411
|View full text |Cite
|
Sign up to set email alerts
|

ERK2-Pyruvate Kinase Axis Permits Phorbol 12-Myristate 13-Acetate-induced Megakaryocyte Differentiation in K562 Cells

Abstract: Background: Pyruvate kinase plays a crucial role in tumor cell proliferation, however, its role in differentiation is relatively unelucidated. Results: PKM2 and PKR dependent metabolic switch toward energy production and nuclear translocation of PKM2 was observed during megakaryocyte differentiation. Conclusion: ERK2 controlled status of PK isoforms is essential for megakaryocytic differentiation. Significance: Metabolic shift impact the process of differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…However, in this study, we only found that PKM2 is highly expressed in moderately differentiated HCC (Figure 7E, 7F; Table 2). This is somewhat in line with two previous findings: one is that PKM2 expression is upregulated in PMA-induced megakaryocytic differentiation and that PKM2 silencing inhibits its differentiation in leukemia [36]. The other is the interaction of PKM2 with Oct4, a major regulator of self-renewal and differentiation in stem cells, decreases the transcriptional activity of Oct4 for ‘stemness’ maintaining of glioma stem cells and thus induces differentiation [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in this study, we only found that PKM2 is highly expressed in moderately differentiated HCC (Figure 7E, 7F; Table 2). This is somewhat in line with two previous findings: one is that PKM2 expression is upregulated in PMA-induced megakaryocytic differentiation and that PKM2 silencing inhibits its differentiation in leukemia [36]. The other is the interaction of PKM2 with Oct4, a major regulator of self-renewal and differentiation in stem cells, decreases the transcriptional activity of Oct4 for ‘stemness’ maintaining of glioma stem cells and thus induces differentiation [37].…”
Section: Discussionsupporting
confidence: 91%
“…We found in this study that hypoxia induces increased expression of the PKM2 protein, but not PKL or PKM1 in liver cancer cell lines (Figures 6, S3). This mirrors the early observation that PKM2 mRNA is up-regulated in hypoxia-treated hepatoma cells [36]. There are three possible mechanism underlying PKM2 overexpression in hypoxic cells.…”
Section: Discussionsupporting
confidence: 86%
“…ERK1/2 is largely involved in megakaryocytic differentiation, the phosphorylation of ERK1/2 triggers megakaryocytic differentiation . It was shown that the phosphorylation of ERK1/2 (p‐ERK1/2) was increased after incubation with ee‐As 4 S 4 (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…A). Since PMA is known to stimulate NF‐κB p65 subunit and PKM2 dimerization (Amini et al, ; Kaminski et al, ; Chaman et al, ), we assessed whether PMA could modulate the synergistic effects observed with PKM2 and p65 overexpression. The results showed that PMA alone induced HIV‐1 LTR activity by 16‐fold (Fig.…”
Section: Resultsmentioning
confidence: 99%